GaN film and preparation method and application thereof
Through the combination of low-temperature pulsed laser deposition and high-temperature organic metal chemical vapor deposition technology, the problems of high cost and poor uniformity of GaN films were solved, and GaN films with controllable thickness and good crystallinity were prepared, which are suitable for the fields of photoelectronics and microelectronics. Large-scale application.
Patent Information
- Application Number
- CN202411198868.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The existing GaN film preparation methods have problems of high production costs and poor growth uniformity, which limits their application in the fields of photoelectronics and microelectronics.
AlN films were deposited by low-temperature pulsed laser deposition process, combined with high-temperature organometallic chemical vapor deposition process, and by depositing GaN films on AlN or MoS2 films, adjusting operating parameters to achieve a GaN film preparation with controllable thickness and good crystallization.
It realizes low-cost, simple and easy-to-operate GaN film preparation, significantly reducing dislocation density, and is suitable for large-scale applications.
Smart Images

Figure CN119121137A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and in particular to a GaN film and a preparation method and application thereof. Background Art
[0002] Gallium nitride (GaN) is a wide bandgap semiconductor material with a bandgap of up to 3.4eV. Devices made from it have the advantages of large photocurrent, high sensitivity, high RF power density, and high UV / visible light suppression rate, and have broad application prospects in the fields of photodetectors and transistors. Therefore, it is of great significance to prepare GaN films with uniform growth, controllable thickness and good crystallization. At present, the common method for preparing GaN films is organic metal chemical vapor deposition (MOCVD), which has the advantages of relatively simple equipment, fast growth rate, and short growth cycle. However, it also has the problems of high production cost, high dislocation density of the grown GaN films (poor uniformity of GaN films), etc., which seriously limits the practical application of GaN materials in the fields of optoelectronics and microelectronics.
[0003] Therefore, it is of great significance to develop a simple, easy-to-operate, and low-cost method for preparing GaN thin films, and to prepare GaN thin films with controllable thickness, good crystallization, and uniform growth. Summary of the invention
[0004] The purpose of the present invention is to provide a GaN film and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a GaN thin film comprises the following steps:
[0007] 1) Using AlN ceramic target as raw material, AlN film is deposited on substrate by pulsed laser deposition process;
[0008] Alternatively, an AlN ceramic target is used as a raw material, and an AlN film is deposited on a substrate by a pulsed laser deposition process, and then a MoS2 film is deposited on the AlN film by a magnetron sputtering process using metal Mo and sulfur powder as raw materials;
[0009] 2) Using trimethylgallium, trimethylaluminum and ammonia as raw materials, a GaN film is deposited on an AlN film or a MoS2 film by adopting an organic metal chemical vapor deposition process.
[0010] Preferably, the substrate in step 1) is one of a Si substrate, an Al2O3 substrate, a SiO2 / Si substrate, and an InGaN substrate.
[0011] Preferably, in step 1), the substrate is cleaned and annealed before use.
[0012] Preferably, the specific operation of the cleaning includes: first cleaning the substrate with a H2SO4-H2O2 aqueous solution, and then cleaning the substrate with a HF solution with a mass fraction of 3% to 7%. The function of cleaning the substrate is to remove pollutants on the surface of the substrate.
[0013] Preferably, the annealing treatment is performed at a temperature of 750° C. to 950° C., and the annealing treatment time is 50 min to 70 min. The annealing treatment is used to remove residual contaminants on the surface of the substrate.
[0014] Preferably, the operating parameters of the pulsed laser deposition process (PLD) in step 1) include: substrate temperature of 250°C to 450°C, background pressure of 1mTorr to 4mTorr, laser wavelength of 230nm to 270nm, laser energy of 200mJ to 1000mJ, and plasma generator power of 400W to 500W.
[0015] Preferably, in step 1), the thickness of the AlN film is 80 nm to 120 nm.
[0016] Preferably, the operating parameters of the magnetron sputtering process in step 1) include: a deposition temperature of 600°C to 700°C.
[0017] Preferably, the thickness of the MoS2 film in step 1) is 3nm to 5nm. By magnetron sputtering MoS2 on the AlN film, a surface with better lattice matching with GaN can be obtained, which reduces the problem of lattice mismatch and ultimately makes the uniformity of the GaN film prepared by the metal organic chemical vapor deposition process higher.
[0018] Preferably, the operating parameters of the metal organic chemical vapor deposition process (MOCVD) in step 2) include: a deposition temperature of 990° C. to 1090° C., and a deposition time of 25 min to 45 min.
[0019] Preferably, in step 2), the deposition rate of the GaN film is 3 μm / h to 20 μm / h.
[0020] Preferably, in step 2), the thickness of the GaN film is 1 μm to 5 μm.
[0021] A GaN thin film is made by the above preparation method.
[0022] Preferably, the GaN film is formed by stacking triangular GaN nanosheets.
[0023] Preferably, the GaN thin film is a continuous thin film.
[0024] Preferably, the GaN thin film is a single crystal thin film.
[0025] An electronic product comprising the GaN thin film.
[0026] Preferably, the electronic product is a field effect transistor.
[0027] The beneficial effects of the present invention are as follows: the present invention organically combines low-temperature PLD and high-temperature MOCVD to prepare GaN thin films, which has the advantages of being simple and easy to operate, low cost, and suitable for mass production. The prepared GaN thin films have smooth surfaces, controllable thickness (the thickness can be adjusted within the range of 1 μm to 5 μm), good crystallization, and uniform growth (dislocation density is significantly reduced), and are suitable for large-scale applications in the optoelectronics and microelectronics fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the pulsed laser deposition process in the embodiment.
[0029] Figure 2 Schematic diagram of the metal organic chemical vapor deposition process in the embodiment.
[0030] Figure 3 This is the XRD pattern of the GaN film in Example 1.
[0031] Figure 4 This is the AFM image of the GaN film in Example 1.
[0032] Figure 5 This is the SEM image of the GaN film in Example 1.
[0033] Figure 6 This is the XRD diagram of the GaN film in Example 2.
[0034] Figure 7 Schematic diagram of the magnetron sputtering process in Example 3.
[0035] Figure 8 Schematic diagram of the structure of the thin film grown on the Si substrate in Example 3.
[0036] Fig. 9 This is the XRD diagram of the GaN film in Example 3.
[0037] Fig.10 This is the AFM image of the GaN film in Example 3.
[0038] Fig.11 This is the SEM image of the GaN film in Example 3.
[0039] Fig.12 This is the XRD diagram of the GaN film in Example 4.
[0040] Fig.13 This is the SEM image of the GaN film in Example 4. DETAILED DESCRIPTION
[0041] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0042] Embodiment 1:
[0043] A GaN thin film, the preparation method of which is as follows:
[0044] 1) A Si substrate (square, 2 cm × 2 cm in size) was first cleaned with a H2SO4-H2O2 aqueous solution (the mass ratio of H2SO4, H2O2, and water was 3:1:1) for 3 min, then cleaned with a 5% HF solution for 3 min, and then placed in a pulsed laser deposition device and annealed at 750 °C for 50 min. A radio frequency plasma generator was used to generate nitrogen plasma, and K r F excimer laser ablation sintering AlN ceramic target deposited AlN film with thickness of 100nm on substrate. The operation parameters of pulse laser deposition process were: substrate temperature of 250℃, background pressure of 1mTorr, laser wavelength of 248nm, laser energy of 200mJ, and power of RF plasma generator of 400W (schematic diagram of pulse laser deposition process is shown in Figure 1 shown);
[0045] 2) The Si substrate with AlN film deposited thereon obtained in step 1) (two substrates are placed opposite to each other) is placed in a heating furnace (model: OTF-1200X, Hefei Kejing Material Technology Co., Ltd.), and then 0.2 g of trimethylgallium (TMGa) and 0.2 g of trimethylaluminum (TMAl) are placed in the heating furnace, the distance between trimethylgallium and trimethylaluminum and the Si substrate is L1, and the distance between the Si substrate and the edge of the heating furnace is L2. The parameters of the heating furnace are set: reaction temperature T = 990 ° C; heating rate The rate is 20℃ / min; when the temperature in the heating furnace is 800℃, the gas is introduced, the reaction gas pressure p=1000Pa; the N2 flow rate is 15sccm; the NH3 flow rate is 30sccm; L1=12cm; L2=5.5cm; the reaction time is 35min; the substrate spacing d=60mm, the heating furnace is started, and a mixture of N2 and NH3 is introduced from the gas inlet on one side of the heating furnace to deposit a GaN film on the AlN film (the schematic diagram of the metal organic chemical vapor deposition process is shown in Figure 2 shown).
[0046] Performance Testing:
[0047] The X-ray diffraction (XRD) pattern of the GaN film in this embodiment is as follows: Figure 3As shown, the atomic force microscope (AFM) image of the GaN film in this embodiment is as follows Figure 4 As shown, the scanning electron microscope (SEM) image of the GaN film in this embodiment is as follows Figure 5 shown.
[0048] Depend on Figure 3 and Figure 4 It can be seen that a GaN film is indeed prepared in this embodiment, and the purity of the GaN film is relatively high.
[0049] Depend on Figure 5 It can be seen that the GaN film in this embodiment is a continuous single crystal film formed by stacking triangular GaN nanosheets together. The thickness of the film is 2 μm, the roughness is 0.54 nm, and the half-height width is 159 arcsec.
[0050] Embodiment 2:
[0051] A GaN thin film, the preparation method of which is as follows:
[0052] 1) A Si substrate (square, 2 cm×2 cm in size) was first cleaned with a H2SO4-H2O2 aqueous solution (the mass ratio of H2SO4, H2O2, and water was 3:1:1) for 3 min, then cleaned with a 5% HF solution for 3 min, and then placed in a pulsed laser deposition device (same as in Example 1), annealed at 950° C. for 70 min, and then nitrogen plasma was generated using a radio frequency plasma generator, and K r F excimer laser ablation sintering AlN ceramic target deposited AlN film with thickness of 100nm on substrate. The operation parameters of pulsed laser deposition process were as follows: substrate temperature of 450℃, background pressure of 2mTorr, laser wavelength of 248nm, laser energy of 300mJ, and power of RF plasma generator of 500W.
[0053] 2) Place 0.15 g of trimethylgallium (TMGa) and 0.15 g of trimethylaluminum (TMAl) into a heating furnace (same as in Example 1) on the Si substrate deposited with the AlN film obtained in step 1), the distance between trimethylgallium and trimethylaluminum and the Si substrate is L1, the distance between the Si substrate and the edge of the heating furnace is L2, and the parameters of the heating furnace are set: reaction temperature T = 1040°C; heating rate is 20°C / min; when the temperature in the heating furnace is 800°C, gas is introduced, and the reaction gas pressure p = 2000Pa; N2 flow rate is 20sccm; NH3 flow rate is 40sccm; L1 = 15cm; L2 = 4cm; reaction time is 30min; substrate spacing d = 80mm, start the heating furnace, and introduce a mixed gas of N2 and NH3 from the gas inlet on one side of the heating furnace to deposit a GaN film on the AlN film.
[0054] Performance Testing:
[0055] The XRD pattern of the GaN film in this embodiment is as follows: Figure 6 shown.
[0056] Depend on Figure 6 It can be seen that a GaN film is indeed prepared in this embodiment, and the purity of the GaN film is relatively high.
[0057] In addition, it has been tested (the testing method is the same as that of Example 1) that the GaN film in this example is a continuous single crystal film formed by stacking triangular GaN nanosheets together, the thickness of the film is 3 μm, and the half-height width is 168 arcsec.
[0058] Embodiment 3:
[0059] A GaN thin film, the preparation method of which is as follows:
[0060] 1) A Si substrate (square, 2 cm×2 cm in size) was first cleaned with a H2SO4-H2O2 aqueous solution (the mass ratio of H2SO4, H2O2, and water was 3:1:1) for 3 min, then cleaned with a 5% HF solution for 3 min, and then placed in a pulsed laser deposition device (same as in Example 1), annealed at 800° C. for 55 min, and then nitrogen plasma was generated using a radio frequency plasma generator, and K r F excimer laser ablation sintering AlN ceramic target deposited AlN film with a thickness of 100nm on the substrate. The operating parameters of the pulsed laser deposition process were: substrate temperature of 400℃, background pressure of 3mTorr, laser wavelength of 248nm, laser energy of 250mJ, and power of RF plasma generator of 500W.
[0061] 2) The Si substrate with AlN film deposited thereon obtained in step 1) is placed in a CVD tube furnace, with metal Mo as the target material and Ar gas as the supply gas and the gas pressure maintained at 0.7 Pa, and magnetron sputtering is performed (the schematic diagram of the magnetron sputtering process is shown in FIG. Figure 7 The deposition of metallic Mo on non-polar a-plane GaN was carried out by the method shown in the figure. Sulfur powder (200 mg) was used as the source of S element and N2 was used as the carrier gas. The S powder was converted into a gaseous precursor by heating in a CVD tube furnace. 10 sccm of N2 was introduced to transfer the S gas to the surface of the AlN film. The film was then kept at 680°C for 1 hour to form a MoS2 film with a thickness of 4 nm.
[0062] 3) The Si substrate (two substrates are placed opposite to each other) deposited with the MoS2 film obtained in step 2) is placed in a heating furnace (same as in Example 1), and then 0.1g of trimethylgallium (TMGa) and 0.1g of trimethylaluminum (TMAl) are placed in the heating furnace, the distance between trimethylgallium and trimethylaluminum and the Si substrate is L1, and the distance between the Si substrate and the edge of the heating furnace is L2. The parameters of the heating furnace are set: reaction temperature T = 1000°C; heating rate is 20°C / min; when the temperature in the heating furnace is 800°C, gas is introduced, and the reaction gas pressure p = 5000Pa; N2 flow rate is 12sccm; NH3 flow rate is 20sccm; L1 = 16cm; L2 = 4.5cm; reaction time is 25min; substrate spacing d = 80mm, start the heating furnace, and introduce a mixed gas of N2 and NH3 from the gas inlet on one side of the heating furnace to deposit a GaN film on the MoS2 film (the structural schematic diagram of the film grown on the Si substrate is shown in Figure 8 shown).
[0063] Performance Testing:
[0064] The XRD pattern of the GaN film in this embodiment is as follows: Fig. 9 As shown, the AFM image of the GaN film in this embodiment is as follows Fig.10 As shown, the SEM image of the GaN film in this embodiment is as follows Fig.11 shown.
[0065] Depend on Fig. 9 and Fig.10 It can be seen that a GaN film is indeed prepared in this embodiment, and the purity of the GaN film is relatively high.
[0066] Depend on Fig.11 It can be seen that the GaN film in this embodiment is a continuous single crystal film formed by stacking triangular GaN nanosheets together. The thickness of the film is 5 μm, the roughness is 0.49 nm, and the half-height width is 205 arcsec.
[0067] Embodiment 4:
[0068] A GaN thin film, the preparation method of which is as follows:
[0069] 1) A Si substrate (square, 2 cm×2 cm in size) was first cleaned with a H2SO4-H2O2 aqueous solution (the mass ratio of H2SO4, H2O2, and water was 3:1:1) for 3 min, then cleaned with a 5% HF solution for 3 min, and then placed in a pulsed laser deposition device (same as in Example 1), annealed at 850° C. for 60 min, and then a radio frequency plasma generator was used to generate nitrogen plasma, and K rF excimer laser ablation sintering AlN ceramic target deposited AlN film with thickness of 100nm on substrate. The operation parameters of pulsed laser deposition process were as follows: substrate temperature of 350℃, background pressure of 4mTorr, laser wavelength of 248nm, laser energy of 250mJ, and power of RF plasma generator of 500W.
[0070] 2) The Si substrate with the AlN film deposited thereon obtained in step 1) was placed in a CVD tube furnace (same as in Example 3), and metal Mo was used as a target material, Ar gas was used as a supply gas and the gas pressure was maintained at 0.7 Pa, and metal Mo was deposited on the non-polar a-plane GaN by magnetron sputtering, sulfur powder (200 mg) was used as a source of S element, N2 was used as a carrier gas, and the S powder was converted into a gaseous precursor by heating in a CVD tube furnace, 10 sccm of N2 was introduced to transfer the S gas to the surface of the AlN film, and then the film was kept at 680°C for 1 hour to form a MoS2 film with a thickness of 3 nm;
[0071] 3) The Si substrate (two substrates are placed opposite to each other) deposited with MoS2 film obtained in step 2) is placed in a heating furnace (same as in Example 1), and then 0.1g of trimethylgallium (TMGa) and 0.1g of trimethylaluminum (TMAl) are placed in the heating furnace, the distance between trimethylgallium and trimethylaluminum and the Si substrate is L1, and the distance between the Si substrate and the edge of the heating furnace is L2, and the parameters of the heating furnace are set: reaction temperature T = 1000°C; heating rate is 20°C / min; when the air temperature in the heating furnace is 800°C, gas is introduced, and reaction gas pressure p = 1000Pa; N2 flow rate is 12sccm; NH3 flow rate is 15sccm; L1 = 20cm; L2 = 5cm; reaction time is 30min; substrate spacing d = 80mm, start the heating furnace, and introduce a mixed gas of N2 and NH3 from the gas inlet on one side of the heating furnace to deposit GaN film on the MoS2 film.
[0072] Performance Testing:
[0073] The XRD pattern of the GaN film in this embodiment is as follows: Fig.12 As shown, the SEM image of the GaN film in this embodiment is as follows Fig.13 shown.
[0074] Depend on Fig.12 It can be seen that a GaN film is indeed prepared in this embodiment, and the purity of the GaN film is relatively high.
[0075] Depend on Fig.13 It can be seen that the GaN film in this embodiment is a continuous single crystal film formed by stacking triangular GaN nanosheets together. The thickness of the film is 4 μm and the half-height width is 189 arcsec.
[0076] Embodiment 5:
[0077] A GaN thin film is prepared in the same manner as in Example 4 except that the substrate spacing d in step 3) is adjusted from "80 mm" to "60 mm".
[0078] After testing (the testing method is the same as that of Example 1), the GaN film in this example is a continuous single crystal film formed by stacking triangular GaN nanosheets together, and the thickness of the film is 3 μm.
[0079] Embodiment 6:
[0080] A GaN thin film is prepared in the same manner as in Example 4 except that the substrate spacing d in step 3) is adjusted from "80 mm" to "85 mm".
[0081] After testing (the testing method is the same as that of Example 1), the GaN film in this example is a continuous single crystal film formed by stacking triangular GaN nanosheets together, and the thickness of the film is 4 μm.
[0082] Embodiment 7:
[0083] A GaN thin film is prepared in the same manner as in Example 4 except that the substrate spacing d in step 3) is adjusted from "80 mm" to "100 mm".
[0084] After testing (the testing method is the same as that of Example 1), the GaN film in this example is a continuous single crystal film formed by stacking triangular GaN nanosheets together, and the thickness of the film is 3 μm.
[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a GaN thin film, characterized in that: The following steps are involved: 1) Using AlN ceramic target as raw material, AlN film is deposited on substrate by pulsed laser deposition process; Alternatively, an AlN ceramic target is used as a raw material, and an AlN film is deposited on a substrate by a pulsed laser deposition process, and then a MoS2 film is deposited on the AlN film by a magnetron sputtering process using metal Mo and sulfur powder as raw materials; 2) Using trimethylgallium, trimethylaluminum and ammonia as raw materials, a GaN film is deposited on an AlN film or a MoS2 film by adopting an organic metal chemical vapor deposition process.
2. The method for preparing a GaN thin film according to claim 1, characterized in that: Step 1) The substrate is one of a Si substrate, an Al2O3 substrate, a SiO2 / Si substrate, and an InGaN substrate.
3. The method for preparing a GaN thin film according to claim 1 or 2, characterized in that: Step 1) The operating parameters of the pulsed laser deposition process include: substrate temperature of 250°C to 450°C, background pressure of 1mTorr to 4mTorr, laser wavelength of 230nm to 270nm, laser energy of 200mJ to 1000mJ, and plasma generator power of 400W to 500W.
4. The method for preparing a GaN thin film according to claim 1 or 2, characterized in that: Step 1) The thickness of the AlN film is 80nm to 120nm.
5. The method for preparing a GaN thin film according to claim 1 or 2, characterized in that: Step 1) The operating parameters of the magnetron sputtering process include: a deposition temperature of 600°C to 700°C.
6. The method for preparing a GaN thin film according to claim 1 or 2, characterized in that: Step 1) The thickness of the MoS2 film is 3nm to 5nm.
7. The method for preparing a GaN thin film according to claim 1, characterized in that: Step 2) The operating parameters of the metal organic chemical vapor deposition process include: a deposition temperature of 990° C. to 1090° C. and a deposition time of 25 min to 45 min.
8. The method for preparing a GaN thin film according to claim 1 or 7, characterized in that: Step 2) The thickness of the GaN film is 1 μm to 5 μm.
9. A GaN thin film, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. An electronic product, characterized in that: Comprising the GaN thin film as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing semiconductor single crystal substrate by using two-dimensional crystal transition layer
CN109585269A
METHOD OF MANUFACTURING GaN THIN FILM AND GaN THIN FILM
JP2014154591A
